New digital rights: Imagining additional fundamental rights for the digital era. Issue 44 (April 2022) - Custers, Bart
Abstract : The increasing use of digital technologies by governments and companies raises numerous questions regarding the regulation of these technologies, particularly regarding the rights and legal protections citizens are entitled to. The focus is mostly on the application and potential modification of existing (fundamental) rights. However, the debate and legal research in this area lacks a broader discussion on which new rights citizens should have in the digital era. Only now and then new concepts surface, such as the 'right to be forgotten'. This article deals with the question which new, additional rights could be imagined in the digital era if we were to draft them right now, from scratch, rather than being tied to a set of existing fundamental rights. In order to start a broader legal debate on this, various new rights for citizens in the digital area are proposed.